The Philosophy of Total Quality Management - Chand, Piar; Gupta, Yogesh (Journal of Engineering Education Transformations, 2007)
Total Quality Management (TQM) has assumed a pivotal role in the manufacturing industry as well as in the service sector. Today the market is fiercely competitive; only the fittest can survive and the main yardstick for measuring the fittest is nothing but quality. Corporate success today largely depends on quality. Business firms all over the world have realized that the secret to the superior performance of the Japanese companies has been their concentration on the quality. Hence Total Quality Management (TQM) is no longer thought as a concept. It is a philosophy. The historical evolution of TQM and evolution of TQM related activities in India and projection for future has been traced in this paper. Literature has been reviewed on various definitions of TQM. Implementation of TQM requires a paradigm shift in many facets of organization s functioning that has also been highlighted. On the basis of these philosophies. an integrated TQM model has been presented for the successful implementation of TQM.